Sacred Temporality, Homecoming, and Religious Magical Realism in Danarto’s Indonesian Fiction Lailatul Qadar - Al Banna, Dzar (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2025)
This article examines how Danarto’s short story Lailatul Qadar transforms the culturally familiar experience of mudik (homecoming) into a religiously charged magical realist narrative. The study asks how the story constructs an empirically recognisable social world, how it introduces irreducible supernatural phenomena without collapsing into fantasy, and how its narrative form turns late-Ramadan mobility into a site of ontological uncertainty. This study adopts a qualitative textual case study grounded in close reading, document analysis, Wendy B. Faris’s theory of magical realism, and Gérard Genette’s narratology. The analysis focuses on five dimensions: the phenomenal world, irreducible magical elements, unsettling doubts, the merging of realms, and disruptions of time, space, and identity, while also tracing focalization, voice, temporal sequencing, and symbolic imagery. The findings show that Danarto does not merely append miracle to realism; he narratively fuses everyday piety, transport infrastructures, family intimacy, and sacred temporality into what this article terms religious remystification. Mudik appears not only as social mobility but as a threshold through which divine presence, angelic mediation, and spiritual testing become narratively legible. The article argues that Lailatul Qadar expands the discussion of magical realism in Indonesian literature by showing that its enchantment may emerge from Islamic sacred time rather than from folklore alone. It also demonstrates that intrinsic elements become analytically productive when read as narrative devices that organize religious ambiguity rather than as isolated formal components.